Adventitial inflammation and its interaction with intimal atherosclerotic lesions - Akhavanpoor, Mohammadreza; Wangler, Susanne; Gleissner, Christian A.; Korosoglou, Grigorios; Katus, Hugo A.; Erbel, Christian (Frontiers in Physiology, 2014)
The presence of adventitial inflammation in correlation with atherosclerotic lesions has been recognized for decades. In the last years, several studies have investigated the relevance and impact of adventitial inflammation on atherogenesis. In the abdominal aorta of elderly Apoe-/- mice, adventitial inflammatory structures were characterized as organized ectopic lymphoid tissue, and therefore termed adventitial tertiary lymphoid organs (ATLOs). These ATLOs possess similarities in development, structure and function to secondary lymphoid organs. A crosstalk between intimal atherosclerotic lesions and ATLOs has been suggested, and several studies could demonstrate a potential role for medial vascular smooth muscle cells in this process. We here review the development, phenotypic characteristics, and function of ATLOs in atherosclerosis. Furthermore, we discuss the possible role of medial vascular smooth muscle cells and their interaction between plaque and ATLOs.